On the importance of the iceberg technique or theory of omission as a narrative resource - Huárag Álvarez, Eduardo (2024)
Following the definition of the “iceberg” theory, or theory of omission, we analyze its application in short stories and novels. The aim is to demonstrate its impact on the handling of suspense through its integration into the structure of fiction. As we shall see, the theory of omission influences the management of suspense, depending on the author’s creativity and the judicious withholding of information. In some cases, such information is entirely omitted. Thus, the iceberg theory is realized, an element that reveals only a fraction of its entirety, and by applying this principle, the primary event or incident remains elusive.